Accountable: The True Story Of A Racist Social Media Account and The Teenagers Whose Lives It Changed - Slater, Dashka (New York, NY : Farrar Straus Giroux Books for Young Readers, 2023)
A young adult nonfiction book on how Albany High School handles a racist social media incident that incurs lasting and devastating consequences
Keywords: Albany High School (Albany, Calif.)--Juvenile literature; Social media--Influence--California--Juvenile literature; Racism in education--California--Juvenile literature; Educational accountability--California--Juvenile literature